Pelatihan Pengolahan Sampah Plastik Untuk Meningkatkan Kesadaran Masyarakat Kelurahan Kerten Akan Bahaya Sampah Plastik dengan Langkah Berkelanjutan - Prihadi, Singgih; Yogatama, Muhamad Andito; Rachmansyah, Anfika; Shefiani, Nadia; Eka Karistalia, Novilalia; Sari, Novita Vetika; Viola Khalifah, Pradivta; Widyastuti, Ratna; Cardinalia, Rheigi Shaula; Azzahra, Sabrilla Almas; Azilia, Wika (Society : Jurnal Pengabdian Masyarakat, 2023)
Community activities are not far from garbage, even in every activity there is always trash. If the waste we produce is not managed properly it will have an impact on the environment and this will also have an impact on us. To prevent and overcome this, Sebelas Maret University KKN students carry out a community service program in the form of socialization activities and training in managing plastic waste into products that have economic value in the form of a ruler. This community training activity uses lecture, demonstration, and practice methods. The purpose of this activity is so that residents of the Kerten sub-district can continue to develop creativity and innovation in processing household waste, especially plastic. The results obtained from this activity are enthusiasm from the training participants so that they can foster their creativity and innovation in plastic waste management, open to knowledge about the dangers of plastic waste to life and increase skills in plastic waste management.